The Fluid Evolution of Ancient Carbonate Reservoirs in Sichuan Basin and Its Implication for Shale Gas Exploration - Zhou, Zhenzhu; Chen, Xiaolan; Xia, Haiyang (Frontiers in Earth Science, 2021)
Sichuan Basin is the only successful basin for shale gas exploration in China. In addition to the main shale in the Lower Silurian Longmaxi formation, the lower Cambrian Qiongzhusi shale is an important potential formation. However, it was once considered that shale gas is difficult to enrich because of its poor sealing conditions and hydrocarbon migration to adjacent reservoirs. With the increasing research on hydrocarbon generation and reservoir in shale of Qiongzhusi Formation in recent years, it has become an important exploration target in Sichuan Basin. The enrichment of oil and gas is closely related to fluid activities. Limited by the degree of exploration, there is little analysis of fluid activities in Qiongzhusi formation, and there is little analysis of shale gas enrichment potential from the perspective of fluid. The hydrocarbon generated from Qiongzhusi shale in the rift could migrate laterally to the uplift area and form a reservoir in Dengying Formation. The fluid activities from source rock to reservoir are basically the same. Therefore, this paper restored the history of hydrocarbon activities in Dengying reservoirs based on fluid inclusion analysis. Then the fluid activities process in Qiongzhusi shale was studied, and its enrichment conditions of shale gas was discussed. The results show that the hydrocarbon activities of Dengying Formation can be divided into three stages: 1) oil charging stage, 2) oil cracking gas generation stage and 3) gas reservoir adjustment stage. The first stage is under normal pressure, and the second and third stages developed overpressure with pressure coefficients of 1.3 and 1.2, respectively. High pressure coefficient is an important indicator of shale gas enrichment. Because the source rock of Qiongzhusi formation has always been the main source rock of Dengying Formation, it can supply hydrocarbon to Dengying Formation only with overpressure in gas generation stage. Therefore, overpressure in the last two stages of gas generation certainly existed. As long as the sealing condition of shale itself is not particularly poor, shale gas “sweet points” would be formed. Therefore, the thick shale in Deyang-Anyue rift is the focus of shale gas exploration in Qiongzhusi